The Students’ Perceptions on Using Blended Learning for English Learning during Covid-19 Pandemic - Istiqomah Istiqomah (Yayasan Visi Intan Permata, 2021)
The policy of remote learning (PJJ) during the COVID-19 pandemic caused new problems for the students. The Implementation of the teaching and learning process has totally changed from face-to-face into online learning and some schools tried to integrate offline and online learning. This research objective was to see the students’ perception of the use of blended learning in English classes. The Subject of this study is Mechanical Engineering Students 4th Semester of STTR Cepu. This study uses a descriptive quantitative design. The researcher took data from a questionnaire on the students' perceptions in the use of blended learning which was consisted of 19 questions and an observation checklist to crosscheck the students’ answers in the questionnaire. Then, analyzing the data descriptively and measuring it using a Likert scale. The results of the study showed the students’ positive response toward the implementation of blended learning since it has great benefit in the teaching and learning process. The implementation of the blended learning method in English lessons required the teachers’ creativity in providing an English learning platform. This research also revealed the weaknesses of Blended Learning. The success of the implementation of blended learning depended on the availability of the facilities like internet access and network in applying that method. In addition, the knowledge of using technology was necessarily mastered by the teachers and the students.